A Smart Multifunctional Nanoparticle for Enhanced Near-Infrared Image-Guided Photothermal Therapy Against Gastric Cancer [Corrigendum] - Shao J (Dove Medical Press, 2021)
Shao J, Liang R, Ding D, Zheng X, et al. Int J Nanomedicine. 2021;16:2897–2915. The authors have advised due to an error at the time of figure assembly, Figure 8F on page 2911 is incorrect. The correct Figure 8 is shown below. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article